(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Cross-sections of leaf blades and petioles of different strawberry genotypes exhibiting different levels of resistance to Chaetosiphon fragaefolii were studied using the paraffin method, and staining with safranin, crystal violet and light green. Besides thicker cell walls of the cortex collenchyma in the more resistant genotypes, and a proportionally wider collenchyma than parenchyma in the cortex, their midribs are also encircled by a ring of more intensely stained lignified cells forming a physical ring. This stain reaction of cells to safranin and crystal violet occurs also in lateral vascular bundles, as well as in leaf palisade tissue. The tissue cross-sections of the sensitive genotypes revealed a predominance of green on the cellulose cell walls and protoplasts due to the reaction to light green SF, while stain reactions to safranin and crystal violet were not evidenced.